Iowa Birdline update, December 17, 1990 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1990)
Email of the Iowa Birdline update for December 17, 1990. Highlights of the update include a sighting of a Varied Thrush and summaries of Christmas bird counts from around the state. Many species were counted and several excellent birds were observed during the Christmas censuses, including a possible Least Flycatcher, Black Scoters, Horned Grebes, and a Townsend's Solitaire. Also included are handwritten notes indicating the continued presence of a Least Flycatcher and a Western Grebe. Epson - sheet feed/flatbed